Site dependence of the Kondo scale in CePd1-xRhx due to Pd-Rh disorder - Stockert, U.; Hartmann, S.; Deppe, M.; Caroca-Canales, N.; Sereni, J.G.; Geibel, C.; Steglich, F.; Sereni, Julián (American Physical Society, 2015)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina